HELPLESSNESS EFFECTS ON THE MAIN CHARACTER’S FATE ACCEPTANCE IN NEVER LET ME GO - Larasati, Syafa Khairina; Thohiriyah (Esteem Journal of English Education Study Programme, 2025)
This research explores the pervasive impact of learned helplessness on various aspects of Kathy H.’s life in Kazuo Ishiguro’s Never Let Me Go, particularly focusing on her role as an organ donor and her interpersonal relationships. Employing close reading and library research methods, the study engages with Boddez et al.’s (2022) framework of learned helplessness to analyze how dystopian structures intensify psychological resignation and foster passive acceptance of fate. The novel reveals how Kathy H., a clone conditioned for organ donation, internalizes powerlessness in the face of inescapable circumstances. Her emotional experience marked by detachment, burnout, and chronic emotional fatigue reflect the broader psychological toll of living within a system that denies autonomy and agency. The illusion of protection within the educational institution and the characters’ limited control over their lives illustrate how systemic control cultivates helplessness. This study argues that the normalization of powerlessness within such a dystopian context leads Kathy to quietly embrace her predetermined function, shedding light on the insidious effects of institutionalized control on self-perception and agency. Ultimately, the analysis offers a nuanced understanding of how helplessness is generalized beyond singular experiences to shape one’s entire psychological landscape in oppressive systems.